戶外教育課程評估指標建構之研究 Indicators for Evaluating Outdoor Education Curricula - 鄭智明 Chi Meng Cheang; 陳美燕 Mei-Yen Chen; 郭雄軍 Husing-Chun Kuo (Journal of Research in Education Sciences)
國民基本教育之課程發展本於全人教育的精神，強調學生是自發主動的學習者，學校教育應循循善誘，激發學生的學習動機與熱情，引導學生妥善開展與自我、他人、社會及與自然的各種互動能力。本研究目的在建構學校結合教育目標下實施戶外教育課程的評估指標，為戶外教育課程在學校開展制定基礎樣式，以促進學校教育與戶外教育之融合發展。研究方法分為兩部分，先以文獻分析法與系統性文獻回顧法，針對近10年國內外學者對學校實施戶外教育課程相關學術成果進行分析，再以臺灣先前建構之實施戶外教育指標為基礎，透過深度訪談法取得學者專家的建議建構並修正指標。本研究初步收錄8,099篇文獻，依據納入與排除標準篩選後納入190篇期刊論文進行分析，依據系統性文獻回顧分析結果，結合國際與不同區域戶外教育發展特徵和課程評估之角度，整合具系統性之學校戶外教育課程評估架構層次，包括課程規劃與組織、課程設計與發展、課程實施與教學、課程成效與優化、課程安全風險管理機制等五大構面與15個向度。接著，深度訪談結果歸納出46個細目指標，並以三角 檢測與專家效度呈現研究信實度。本研究結論為戶外教育課程評估的學術與實務價值提供理論依據，對華人社會戶外教育課程的發展方向具重大的啟示意義。 Background and Research Objectives Taiwan’s national basic education curriculum was developed on the basis of the principles of whole-person education. According to these principles, students should be self-motivated and active learners and schools should foster students’ learning motivation and enthusiasm and help them cultivate their abilities to meaningfully interact with themselves, others, society, and nature. In this study, a framework was developed for evaluating outdoor education programs. The goal was to develop a basic model for the integration of outdoor education with school-based education. This study was conducted in two steps. First, the literature was reviewed to identify relevant international and Taiwanese articles published within the last decade. Second, on the basis of established indicators of the implementation of outdoor education programs in Taiwan, in-depth interviews were conducted with experts to gather feedback for developing and refining the indicators. Literature Review Bisson (1996) introduced a metaphorical model called the Outdoor Education Umbrella. In this model, the handle of the umbrella represents camping education, symbolizing its foundational role as a precursor to outdoor education. The canopy represents experiential education, symbolizing its universality across all outdoor experiential learning methods. As an overarching framework, experiential education is applied in all methods of outdoor experiential learning. The left side of the Outdoor Education Umbrella focuses on outdoor experiential learning methods for self-development (Outdoor Adventure Education, Challenge Education, and Adventure Education), whereas the right side focuses on methods for personal and environmental ethical development (Environmental Education, Earth Education, and Wilderness Education). Conventional education, characterized by a transfer of current knowledge and skills through formal schooling, often neglects the individual needs of learners. Therefore, Dewey (1938) advocated for a revolution in education, focusing on the concept of “learning by doing,” which emphasizes grounding education in learners’ present experiences. Waite et al. (2016) highlighted that outdoor education confers multifaceted benefits covering academic, personal, social, and psychological aspects; the researchers indicated that outdoor education enhances learning interest, motivation, and outcomes. Orda and Leather (2011) suggested that Dewey’s experiential learning, which focuses on “meaning” and “learning potential,” can deepen the meaning derivable through outdoor education. This study highlighted a close association between outdoor education and experiential learning. Unlike other educational approaches, outdoor education involves leveraging outdoor environments to foster human–nature interactions, thereby conferring psychological, physiological, social, and educational benefits; this is the most unique feature of outdoor education. The outdoor education model explored in the current study was developed on the basis of experiential learning. This model integrates elements of adventure and environmental awareness from Outdoor Adventure Education and Environmental Education, respectively. Methods This study was conducted in two steps. First, a systematic review of the literature was conducted to identify publications by Taiwanese and international scholars on the implementation of outdoor education curricula in schools over the last decade. Second, on the basis of established indicators of the implementation of outdoor education curricula in Taiwan, in-depth interviews were conducted with purposively selected experts. These interviews offered expert insights for the development and refinement of the indicators. Results and Discussion Initially, 8,099 articles were identified. From these, 190 articles were selected on the basis of predefined criteria. Then, a systematic review of the literature was performed. On the basis of the results, a comprehensive framework was developed for evaluating outdoor education programs in schools by combining the characteristics of outdoor education within international and regional contexts with the perspectives of program evaluation. This framework had 5 dimensions and 15 facets: program planning and organization, program design and development, program implementation and teaching, program effectiveness and optimization, and program safety and risk management mechanisms. A total of 46 indicators were selected by analyzing the interview data. The reliability of the results was ensured through triangulation and expert verification. The characteristics of international and regional outdoor education frameworks were aligned with school operations and curriculum systems; thus, key connotations and features of outdoor education in schools were identified. First, outdoor education is a vital component of school education. Second, it is a crucial method for fostering holistic development in students. Third, outdoor education reflects the integration of national and regional policies, cultural exchanges, and developmental trends. Fourth, it leverages social resources. Finally, safety and risk management mechanisms are consistently embedded throughout the curriculum of outdoor education. Furthermore, a systematic framework for teacher development is established. Conclusion, Contributions, and Implications To implement outdoor education programs across grades in an orderly manner, government authorities or school leadership must first recognize the benefits of outdoor education, which are well-supported. The second step is to formulate policies and regulations that enable schools to design outdoor education programs reflecting the traditional characteristics and geographic features of a given country, region, and individual school. Furthermore, a system for training outdoor education teachers must be established to support these programs. Concurrently, awareness of the safety risks associated with implementing outdoor education programs should be increased. The comprehensive and systematic indicators proposed in this study can serve as a foundation for reviewing and updating the evaluation criteria for outdoor education programs in alignment with national education policies and school needs. Furthermore, these indicators may guide the development of outdoor education programs in schools.